Ice-stream dynamics: the coupled flow of ice sheets and subglacial meltwater - Kyrke-Smith, T (2014)
Ice sheets are among the key controls on global climate and sea level. A detailed understanding of their dynamics is crucial to make accurate predictions of their future mass balance. Ice streams are the dominant negative component in this balance, accounting for up to 90% of the Antarctic ice flux into ice shelves and ultimately into the sea. Despite their importance, our understanding of ice-stream dynamics is far from complete. A range of observations associate ice streams with meltwater. Meltwater lubricates the ice at its bed, allowing it to slide with less internal deformation. It is believed that ice streams may appear due to a localisation feedback between ice flow, basal melting and water pressure in the underlying sediments. This thesis aims to address the instability of ice-stream formation by considering potential feedbacks between the basal boundary and ice flow. Chapter 2 considers ice-flow models, formulating a model that is capable of capturing the leading-order dynamics of both a slow-moving ice sheet and rapidly flowing ice streams. Chapter 3 investigates the consequences of applying different phenomenological sliding laws as the basal boundary condition in this ice-flow model. Chapter 4 presents a model of subglacial water flow below ice sheets, and particularly below ice streams. This provides a more physical representation of processes occurring at the bed. Chapter 5 then investigates the coupled behaviour of the water with the sediment, and Chapter 6 the coupled behaviour of the water with the ice flow. Under some conditions this coupled system gives rise to ice streams due to instability of the internal dynamics.